Flow cytometric analysis of inflammatory and resident myeloid populations in mouse ocular inflammatory models. (October 2016) - Liyanage, Sidath E.; Gardner, Peter J.; Ribeiro, Joana; Cristante, Enrico; Sampson, Robert D.; Luhmann, Ulrich F.O.; Ali, Robin R.; Bainbridge, James W.
Abstract: Myeloid cells make a pivotal contribution to tissue homeostasis during inflammation. Both tissue-specific resident populations and infiltrating myeloid cells can cause tissue injury through aberrant activation and/or dysregulated activity. Reliable identification and quantification of myeloid cells within diseased tissues is important to understand pathological inflammatory processes. Flow cytometry is a valuable technique for leukocyte analysis, but a standardized flow cytometric method for myeloid cell populations in the eye is lacking. Here, we validate a reproducible flow cytometry gating approach to characterize myeloid cells in several commonly used models of ocular inflammation. We profile and quantify myeloid subsets across these models, and highlight the value of this strategy in identifying phenotypic differences using Ccr2 -deficient mice. This method will aid standardization in the field and facilitate future investigations into the roles of myeloid cells during ocular inflammation.